Peran Pendidikan Dalam Membentuk Karakter siswa dan Relevasinya diera Globalisasi Menurut Muhammad Iqbal - Putri, Rahma; Utami, Nurfadila (Jurnal Pendidikan Agama Islam, 2024)
This research discusses the role of education in shaping student character and its relevance in the era of globalization based on Muhammad Iqbal's thoughts. In this era full of challenges and rapid change, education has a strategic role in building individual characters who are strong, independent and have moral values. Muhammad Iqbal, a Muslim philosopher and thinker, emphasized the importance of education that does not only focus on cognitive aspects, but also on character formation and spirituality. According to Iqbal, education must encourage students to develop their personal potential optimally, including ethical and spiritual aspects, which are essential in facing the challenges of globalization. This research uses a qualitative approach with a literature study method that examines the concept of education according to Iqbal and its application in the current context of globalization. The research results show that Iqbal's views on education are very relevant in the modern era, where strong character is the key to success in facing global change. It is hoped that these findings can contribute to formulating a character education model that is appropriate to the challenges of the times, as well as becoming a reference for educational practitioners in forming students with strong character and adaptiveness to global change.